Development and Validation of a Spectrophotometric Method for Quantification and Dissolution Studies of Glimepiride in Tablets - Madhusudhanareddy Induri; Bhagavan Raju M.; Rajendra Prasad Y.; Pavankumar Reddy K. (E-Journal of Chemistry)
The objective of present study was to develop and validate an analytical method for quantitative determination and dissolution studies of glimepiride in tablets. The glimepiride shows absorption maxima at 225 nm and obeyed Beer's law in the range of 6.0 – 14.0 µg/mL. The limit of detection and limit of quantitation were 0.06, and 0.17 µg/mL respectively. Percentage recovery of glimepiride for the proposed method ranged from 99.32 to 100.98% indicating no interference of the tablet excipients. It was concluded that the proposed method is simple, easy to apply, economical and used as an alternative to the existing spectrophotometric and non-spectrophotometric methods for the routine analysis of glimepiride in pharmaceutical formulations and in vitro dissolution studies.